1976
DOI: 10.5636/jgg.28.343
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of nitric oxide abundance in equatorial upper atmosphere.

Abstract: The altitude distribution of nitric oxide gamma band emissions in the day airglow was measured by the ultraviolet radiometer aboard a sounding rocket flown early in the morning from Thumba, India. The nitric oxide (NO) concentration could be determined for the first time in the equatorial upper atmosphere in the altitude range between 85 and 140km. The altitude distribution of NO below 105km is similar to those obtained by Meira in 1969 and by the present authors in 1973. The absolute concentration is, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…6. The results from rocket observations of NO at sunrise (SZA=90) by TISONE (1973) and at 07h LT (SZA-82) by TOHMATSU and IWAGAMI (1976) are compared with the theoretical profiles at 07h LT in Fig. 6.…”
Section: Effect Of the Temperature Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…6. The results from rocket observations of NO at sunrise (SZA=90) by TISONE (1973) and at 07h LT (SZA-82) by TOHMATSU and IWAGAMI (1976) are compared with the theoretical profiles at 07h LT in Fig. 6.…”
Section: Effect Of the Temperature Variationmentioning
confidence: 99%
“…It may be concluded that the concentration of odd nitrogen is determined basically by photochemical reactions above 90km in the daytime, whereas the dynamical process has an important effect during the night. TOHMATSU andIWAGAMI (1975) deduced from NO r(1, 0)-airglow observations. Here it must be noted that the observed values have been reduced by a factor 2.07 considering the revision of the fluorescence coefficient for the NO r(l, 0)-band.…”
Section: Photochemistry Of Odd Nitrogen In the Thermospherementioning
confidence: 99%
See 2 more Smart Citations
“…Nitric oxide airglow has been observed mainly through the r-and o-bands in the ultraviolet region (MEIRA, 1971;TISONE, 1973;TOHMATSU andIWAGAMI, 1975, 1976;RUSCH and BARTH, 1975;GERARD, 1975;GERARD and BARTH, 1977). Recently near infrared emission in the 4v=1 and 4v=2 sequences has also been observed by STAIR et al (1975) and by BAKER et al (1977).…”
Section: Introductionmentioning
confidence: 99%